Misclassification in defining and diagnosing microcephaly. Issue 4 (26th July 2019) - Kalmin, Mariah M.; Gower, Emily W.; Stringer, Elizabeth M.; Bowman, Natalie M.; Rogawski McQuade, Elizabeth T.; Westreich, Daniel
Abstract: Background: Several health agencies define microcephaly for surveillance purposes using a single criterion, a percentile or Z‐score cut‐off for newborn head circumference. This definition, however, conflicts with the reported prevalence of microcephaly even in populations with endemic Zika virus. Objective: We explored possible reasons for this conflict, hypothesising that the definition of microcephaly used in some studies may be incompletely described, lacking the additional clinical criteria that clinicians use to make a formal diagnosis. We also explored the potential for misclassification that can result from differences in these definitions, especially when applying a percentile cut‐off definition in the presence of the much lower observed prevalence estimates that we believe to be valid. Methods: We conducted simulations under a theoretical bimodal distribution of head circumference. For different definitions of microcephaly, we calculated the sensitivity and specificity using varying cut‐offs of head circumference. We then calculated and plotted the positive predictive value for each of these definitions by prevalence of microcephaly. Results: Simple simulations suggest that if the true prevalence of microcephaly is approximately what is reported in peer‐reviewed literature, then relying on cut‐off‐based definitions may lead to very poor positive predictive value under realistic conditions. Conclusions: While a simple head circumference criterion may be used in practice as a screening or surveillance tool, the definition lacks clarification as to what constitutes true pathological microcephaly and may lead to confusion about the true prevalence of microcephaly in Zika‐endemic areas, as well as bias in aetiologic studies.